L’immagine come arma. Il ruolo delle fotografie nella protesta di Euromaidan - Tamara Mykhaylyak (EtnoAntropologia)
The Euormaidan’s photos are known all around the world; this event has been described through a myriad of photos and videos. Throughout the exploration and analysis of the major Russian and Ukrainian  journals’ websites, online TVs, social networks and blogs, we have gathered a large amount of visual documents.  Intentionally we focused on the images produced by the protesters and the journalists that supported the protest. We decided to divide the analyzed photos into four categories: conflict, pain, memory and symbols. These categories reveal specific investments made on the photos, roles and functions bestowed to them with the purpose of bolster and strengthen the Euromaidan’s themes.